Project for the Incubation of Small Productive Units Framed in the Values of the Social and Solidarity Economy - Risso, María Cecilia; Tottereau-Díaz, Luciana; Ramassotti, Evangelina (Ingeniería Solidaria, 2015)
This case report describes the analysis of two organizations that work with entrepreneurships: The Center for Entrepreneurs of the Social Economy of the City of Santa Fe (Centro de Emprendedores de la Economía Social de la ciudad de Santa Fe, cees) and the Regional Incubator of Peoples’ Cooperatives of USFCar in Sao Paulo, Brazil. In the context of those experiences, a set of actions being carried out was identified, but which are insufficient for consolidation of the model for integral accompaniment and strengthening. In response to this situation, the authors designed an “Integral Training Program” of training, assistance and accompaniment for entrepreneurs, beginning with the initial stage of enterprise creation and continuing until maturation, to achieve sustainability over time and the capacity for self-management. A detailed description is given of the design of this program. Finally, some recommendations are made to support this type of initiatives, including the design of public policies that encourage and commit contributions from the state budget, and from the academic community, the commitment to transparency and autonomy that would sustain and provide continuity
Keywords: Training; social and solidarity economy; enterprises; incubation; integral program